2022
DOI: 10.1186/s13293-022-00419-1
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of female rats to cardiac arrhythmias following refeeding after severe food restriction

Abstract: Background Many studies have shown malnutrition and inadequate caloric consumption have adverse acute effects on cardiovascular structure and function. Methods To determine the adverse long term cardiovascular effects, we studied cardiac morphology and function in female (F) and male (M) severe food restricted rats 3 months after refeeding (sFR-Refed). Results Two weeks of a normal chow diet in which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Although previous laboratory studies showed that malnutrition could induce arrhythmia in animal models [ 33 , 34 ], the present study first demonstrated that famine is a significant risk for developing bradycardia, atrial fibrillation, and atrioventricular block, not tachycardia, in humans. In the GCF exposure offspring, the chi-square test demonstrated that if subjects had an increased BMI, total cholesterol, blood pressure, or metabolic syndrome, they were more vulnerable in developing bradycardia.…”
Section: Discussionmentioning
confidence: 59%
“…Although previous laboratory studies showed that malnutrition could induce arrhythmia in animal models [ 33 , 34 ], the present study first demonstrated that famine is a significant risk for developing bradycardia, atrial fibrillation, and atrioventricular block, not tachycardia, in humans. In the GCF exposure offspring, the chi-square test demonstrated that if subjects had an increased BMI, total cholesterol, blood pressure, or metabolic syndrome, they were more vulnerable in developing bradycardia.…”
Section: Discussionmentioning
confidence: 59%